Lao PDR Forest Note : Toward Sustainable Forest Landscapes for Green Growth, Jobs, and Resilience - World Bank (World Bank, Washington, DC, 2020)
Natural capital in Lao PDR is a major source of wealth for the country and becomes even more strategic in times of economic stress. While forest products directly benefit vulnerable rural communities, ecosystem services from forests support key economic sectors such as energy, agriculture, industry, and tourism. Forests and downstream industries also offer important job and livelihood opportunities in rural areas in Lao PDR that can be expanded. This country forest note provides an upstream analysis of the status of forests as well as investments and policies relevant to the forest sector in the Lao People’s Demographic Republic. The analysis looks at forests in a programmatic and cross-sectoral manner to strategically position the World Bank Group to support the country in delivering on forest-relevant interventions.